1996
DOI: 10.1111/j.1467-6427.1996.tb00036.x
|View full text |Cite
|
Sign up to set email alerts
|

Cohesion and power in the families of children involved in bully/victim problems at school: an Italian replication

Abstract: A replication was made of the findings of Bowers et al. (1992), relating involvement of children in bully/victim problems at school with characteristics of family systems as revealed by the Family System Test (FAST), on a central Italian sample. The findings regarding father absence, structural plot characteristics -such as use of corners and no separation of figures -and cohesion scores especially with parents, were consistent across both studies; findings relating to power scores were few and inconsistent. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
1
5

Year Published

2000
2000
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(33 citation statements)
references
References 9 publications
(8 reference statements)
2
25
1
5
Order By: Relevance
“…Some studies have found that social deprivation, low father involvement, low parent support or low levels of family cohesion (Hart et al 2000) or harsh and reactive parenting (Barker et al 2008) and maltreatment (Shields and Cicchetti 2001) predicted victimisation. In contrast, others reported that socio-economic status is not related to victimisation (Wolke et al 2001) and that victims more often come from families characterised by high levels of cohesion (Bowers et al 1992), high levels of parental involvement and support (Bowers et al 1992, Baldry and Farrington 1998, Haynie et al 2001, Bowers et al 1994 and parental overprotectiveness (Berdondini and Smith 1996, Georgiou 2008, Perren and Hournung 2005. Finally, studies on family factors and bullying are mainly based on selected and small samples.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have found that social deprivation, low father involvement, low parent support or low levels of family cohesion (Hart et al 2000) or harsh and reactive parenting (Barker et al 2008) and maltreatment (Shields and Cicchetti 2001) predicted victimisation. In contrast, others reported that socio-economic status is not related to victimisation (Wolke et al 2001) and that victims more often come from families characterised by high levels of cohesion (Bowers et al 1992), high levels of parental involvement and support (Bowers et al 1992, Baldry and Farrington 1998, Haynie et al 2001, Bowers et al 1994 and parental overprotectiveness (Berdondini and Smith 1996, Georgiou 2008, Perren and Hournung 2005. Finally, studies on family factors and bullying are mainly based on selected and small samples.…”
Section: Introductionmentioning
confidence: 99%
“…Junger (1996) states that bullying originates from families with problems, erratic parents and from the use of harsh disciplinary methods and authority. Other influences in relation to perpetrators' behaviour have also been proved, such as lack of familiar cohesion, and lack of a paternal figure (Berdondini, 1996;Gibbs y Sinclair, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have found that social deprivation, low father involvement, low parent support or low levels of family cohesion (Hart et al 2000) or harsh and reactive parenting (Barker et al 2008) and maltreatment (Shields and Cicchetti 2001) predicted victimisation. In contrast, others reported that socio-economic status is not related to victimisation (Wolke et al 2001) and that victims more often come from families characterised by high levels of cohesion (Bowers et al 1992), high levels of parental involvement and support (Bowers et al 1992, Baldry and Farrington 1998, Haynie et al 2001, Bowers et al 1994 and parental overprotectiveness (Berdondini and Smith 1996, Georgiou 2008, Perren and Hournung 2005. Finally, studies on family factors and bullying are mainly based on selected and small samples.…”
Section: Introductionmentioning
confidence: 99%